Gangguan Media Sosial bagi Self Regulated Learning Mahasantri Pondok Pesantren Al-Ghozali - Jeny Kusdemawati; Nurus Sa’adah (Institut Agama Islam Negeri Curup, 2023)
The current era of globalization has a significant impact on technological development. Developing technology is also accompanied by advances in social media. The advancement of social media has an impact on excessive attachment to handphone and social media. The method used in this research is a type of qualitative research using interview techniques with four mahasantri as sources. This research was conducted with the aim of knowing how social media affects self-regulated learning in mahasantri. Researchers want to explore more deeply how the picture of self-regulated learning in mahasantri when viewed from activities inside the cottage and outside the cottage, cellphone use, and how to study. The results of this study are that there is a very different picture of Self Regulated Learning in PP Al-Ghozali mahasantri, the picture includes metacognition, learning motivation, and learning behavior. Disruption of learning can occur such as distraction from learning because there are WhatsApp notifications and will continue to scroll through social media such as Youtube Short, Youtube, TikTok and Instagram.